Host Plant Selection Imprints Structure and Assembly of Fungal Community along the Soil-Root Continuum - Fengqiao Li; Zhili Jin; Zichen Wang; Yangwenke Liao; Li Yu; Xiaogang Li (mSystems, 2022)
ABSTRACT The soil fungal community plays pivotal roles in soil nutrient cycling and plant health and productivity in agricultural ecosystems. However, the differential adaptability of soil fungi to different microenvironments (niches) is a bottleneck limiting their application in agriculture. Hence, the understanding of ecological processes that drive fungal microbiome assembly along the soil-root continuum is fundamental to harnessing the plant-associated microbiome for sustainable agriculture. Here, we investigated the factors that shape fungal community structure and assembly in three compartment niches (the bulk soil, rhizosphere, and rhizoplane) associated with tobacco (Nicotiana tabacum L.), with four soil types tested under controlled greenhouse conditions. Our results demonstrate that fungal community assembly along the soil-root continuum is governed by host plant rather than soil type and that soil chemical properties exert a negligible effect on the fungal community assembly in the rhizoplane. Fungal diversity and network complexity decreased in the order bulk soil > rhizosphere > rhizoplane, with a dramatic decrease in Ascomycota species number and abundance along the soil-root continuum. However, facilitations (positive interactions) were enhanced among fungal taxa in the rhizoplane niche. The rhizoplane supported species specialization with enrichment of some rare species, contributing to assimilative community assembly in the rhizoplane in all soil types. Mortierella and Pyrenochaetopsis were identified as important indicator genera of the soil-root microbiome continuum and good predictors of plant agronomic traits. The findings provide empirical evidence for host plant selection and enrichment/depletion processes of fungal microbiome assembly along the soil-root continuum. IMPORTANCE Fungal community assembly along the soil-root continuum is shaped largely by the host plant rather than the soil type. This finding facilitates the implementations of fungi-associated biocontrol and growth-promoting for specific plants in agriculture practice, regardless of the impacts from variations in geographical environments. Furthermore, the depletion of complex ecological associations in the fungal community along the soil-root continuum and the enhancement of facilitations among rhizoplane-associated fungal taxa provide empirical evidence for the potential of community simplification as an approach to target the plant rhizoplane for specific applications. The identified indicators Mortierella and Pyrenochaetopsis along the soil-root microbiome continuum are good predictors of tobacco plant agronomic traits, which should be given attention when manipulating the root-associated microbiome.